Integrating EVS, PV, and ESS in Commercial Parking Lots: A Cooperative Nash Game for Transactive Energy - Hamouda, Mohamed; Elsayed, Youmna; El-Dessouki, M. A.; EL-Shimy, M. (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2026)
Electric vehicles (EVs) are widely recognized as a key solution for reducing emissions in the transportation sector. Their growing adoption, combined with flexible charging schedules, presents a valuable opportunity to enhance grid operations. Unlike traditional approaches, a transactive energy (TE) model provides a more balanced framework, creating mutual benefits for both the grid and EV owners while ensuring that owners retain autonomy to decide how and when their vehicles are charged. In this work, we present a comprehensive TE management framework designed to optimize energy exchange among EVs, photovoltaic (PV) systems, battery energy storage systems (BESS), and the utility grid, addressing the limitations of conventional centralized energy markets. A novel EV parking lot model is proposed, enabling peer-to-peer (P2P) transactions powered exclusively by renewables and the grid, supporting both grid-to-vehicle (G2V) and vehicle-to-grid (V2G) operations to enhance energy utilization. The proposed model enables peer-to-peer (P2P) electricity transactions within a decentralized architecture. To capture the strategic behavior of self-interested energy agents, a game-theoretic approach based on Nash equilibrium is formulated, enabling coordinated decision-making under competitive conditions. The model is implemented using a non-linear programming formulation in GAMS and tested over a 24-hour operational cycle. Comparative analysis between a baseline scenario and the Nash-based model reveals significant improvements in energy utilization, cost-effectiveness, and overall system reliability. The results demonstrate that the proposed cooperative game-theoretic framework not only enhances economic performance but also promotes grid stability and equitable resource allocation, positioning it as a viable solution for future decentralized energy systems.